Impact of perioperative infarcts after cardiac surgery - Patel, Nikil; Horsfield, Mark A.; Banahan, Caroline; Janus, Justyna; Masters, Katie; Morlese, John; Egan, Vincent; Chung, Emma M.L. (American Heart Association, 2015)
Background and Purpose: Brain injury after cardiac surgery is a serious concern for patients and their families. The purpose of this study was to use 3-T fluid attenuated inversion recovery MRI to characterize new and preexisting cerebral ischemic lesions in patients undergoing cardiac surgery and to test whether the accumulation of new ischemic lesions adversely affects cognition.